Deep learning architectures for speech recognition - Yong, Jia Jie (2018)
Choosing which deep learning architecture to perform speech recognition can be laborious. Additionally, improving the performance of a given architecture can require a lot of experimentation. The purpose of this project is to investigate different architectures used in speech recognition tasks and highlight the differences. In addition, the performance impacts of different deep learning techniques, namely DeepSpeech and WaveNet, applied in a recurrent neural network is explored.